Use of Phage Cocktail BFC 1.10 in Combination With Ceftazidime-Avibactam in the Treatment of Multidrug-Resistant Pseudomonas aeruginosa Femur Osteomyelitis—A Case Report - Racenis, Karlis; Rezevska, Dace; Madelane, Monta; Lavrinovics, Ervins; Djebara, Sarah; Petersons, Aivars; Kroica, Juta (Frontiers in Medicine, 2022)
High-energy trauma with severe bone fractures can be complicated by infection, leading to the development of osteomyelitis. P. aeruginosa is an important causative agent of such infections because of its high virulence profile and ability to develop resistance against a wide range of antimicrobials quickly. P. aeruginosa biofilms cause treatment failure and relapsing infections. Bacteriophages are viruses that can be used to treat biofilm-associated infections. Moreover, the combination of phages with certain antimicrobials have demonstrated synergistic and additive effects. We present a case of a 21-year-old patient with relapsing multidrug-resistant (MDR) P. aeruginosa femur osteomyelitis that developed after a road accident, with a proximal right femoral Grade III B open fracture and severe soft tissue damage. Despite extensive antimicrobial treatment and multiple surgical interventions with wound debridement, the infection persisted, with subsequent development of femoral osteomyelitis with a fistula. Patient care management included femoral head excision with wound debridement, intravenous (IV) ceftazidime-avibactam, and the local application of the lytic Pseudomonas bacteriophage cocktail BFC 1.10. Nine months after the intervention, the patient did not show any clinical, radiological, or laboratory signs of inflammation; therefore, hip replacement was performed. Nevertheless, recurrent P. aeruginosa infection evolved at the distal side of the femur and was successfully treated with conventional antimicrobials. In this case, wound debridement combined with antibiotics and bacteriophages resulted in bacterial eradication of proximal femoral segment, avoiding leg amputation, but failed to treat osteomyelitis in distal bone segment. An in vitro assessment of the isolated MDR P. aeruginosa strain for biofilm formation and phage susceptibility was performed. Additionally, the antimicrobial effects of ceftazidime-avibactam and BFC 1.10 were determined on planktonic cell growth and bacterial biofilm prevention was evaluated. The isolated bacterial strains were susceptible to the bacteriophage cocktail. Strong biofilm formation was detected 6 h after inoculation. Ceftazidime-avibactam combined with BFC 1.10 was most effective in preventing planktonic cell growth and biofilm formation. In both cases, the required concentration of ceftazidime-avibactam decreased two-fold. This study demonstrates the possible use of bacteriophages and antibiotics in difficult-to-treat bone and soft tissue infections, where the additive effects of phages and antibiotics were observed.